Effects of Chelating Agents on Mn Absorption by Polygonum pubescens Blume from Mn Ore-containing Soils - Li, J.C.; Xu, D.D.; Xu, Z.F.; Zheng, Z. (Asian Journal of Chemistry, 2015)
Pot experiment was carried out to evaluate the effects of incorporation of various doses of ascorbic acid, tartaric acid and EDTA on the Mn absorption by hyperaccumulator Polygonum pubescens Blume from soil. The results showed that the incorporation of chelating agents could effectively raise the exchangeable Mn content in Mn ore soil, activate Mn in soil and enhance plant Mn uptake. For Mn-activation ability, the order was EDTA > ascorbic acid > tartaric acid. 10 mmol/kg EDTA displayed the maximum effect of 1 135 % on accumulation capacity of the shoots of Polygonum pubescens Blume in mine tailing soils. EDTA is recommended to be coupled with Polygonum pubescens Blume for remediation of Mn ore soils. 5 mmol/kg EDTA was the optimal regulating dose for the Mn transport ability and Mn remediation efficiency of Polygonum pubescens Blume in Mn mine tailing area.